A comparative earnings manipulation analysis using beneish m score and dechow f score: The case of a ZSE selected firm - Kudakwashe Mavengere (Journal of Economic, Business & Accounting Research, 2026)
Background: The study seeks to compare Beneish M Score and Dechow F score proficiency in financial statement fraud detection utilizing a selected Zimbabwe Stock Exchange listed manufacturing firm. Methods: A quantitative research approach was adopted for the study. The Dechow F Score model and Beneish M Score were utilised in the analysis of secondary data of the selected firm from 2011 to 2015 and during the hyperinflation period relevant financial information from 2021 to 2023. The findings were cross validated with Independent external auditor reports. Finding: There exists no fraudulent financial reporting utilising the F Score model from 2011 to 2015 as the F Score was less than 1. The M score attests to non-manipulation from 2011 to 2014, with 2015 -2.009 reveals manipulation of financials but relatively low risk. The year 2023 has an F Score of 1.151 which falls within the above normal risk category. The Independent Auditor Report (IAR) reveals unqualified audit opinion for the years 2021 and 2023. In the year 2022, IAR exposes a qualified audit opinion. The M Score reveals non manipulation in 2021 and 2023 but manipulation detected in 2022. The findings reveal the Beneish M Score has 87.5% accuracy with Dechow F Score 62.5% accuracy. Conclusion: The period under study from 2011 to 2015 and 2021 to 2023 were selected for the study due constant changes to local currency adoption for which relevant financial information was available. Novelty/Originality of this article: The study provides insight into earnings manipulation models (Beneish M Score and Dechow F Score) in normal economic environment as well as hyperinflation. During periods of hyperinflation, the Dechow F score signified financial statements were high risk validating false positives when compared to the Beneish M Score findings that were in line with IAR opinions.